2012
DOI: 10.1016/j.bmc.2011.10.091
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based redesign of an edema toxin inhibitor

Abstract: Edema Factor toxin (EF) of Bacillus anthracis (NIAID category A), and several other toxins from NIAID category B Biodefense target bacteria are adenylyl cyclases or adenylyl cyclase agonists that catalyze the conversion of ATP to 3′,5′-cyclic adenosine monophosphate (cAMP). We previously identified compound 1 (3-[(9-Oxo-9H-fluorene-1-carbonyl)-amino]-benzoic acid), that inhibits EF activity in cultured mammalian cells, and reduces diarrhea caused by enterotoxigenic Escherichia coli (ETEC) at an oral dosage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…For example, β‐lactam antibiotics can increase the production of bacterial toxins in Staphylococcus aureus , while those that inhibit protein synthesis, such as clindamycin, greatly reduce them . As toxins mediate pathogenic effects even after the death of the bacteria, direct inhibitors of bacterial toxins may aid in controlling symptoms when used alone or in combination with antibiotics . Further, as discussed in the next sections, patients may benefit from alternative application modes and cotreatment with antibiotics and other compounds designed to directly target pathways in human cells.…”
Section: Finding New Uses For Approved Drugsmentioning
confidence: 99%
“…For example, β‐lactam antibiotics can increase the production of bacterial toxins in Staphylococcus aureus , while those that inhibit protein synthesis, such as clindamycin, greatly reduce them . As toxins mediate pathogenic effects even after the death of the bacteria, direct inhibitors of bacterial toxins may aid in controlling symptoms when used alone or in combination with antibiotics . Further, as discussed in the next sections, patients may benefit from alternative application modes and cotreatment with antibiotics and other compounds designed to directly target pathways in human cells.…”
Section: Finding New Uses For Approved Drugsmentioning
confidence: 99%
“…As a result, 19 best-scored compounds were tested in a cell assay for their ability to reduce cAMP secretion induced by EF, and it was found that four structurally different compounds inhibited EF in the low micromolar range. Recently, the same group published a study aiming to redesign one of the several initial “hits”, (3-[(9-oxo-9H-fluorene-1-carbonyl)-amino]-benzoic acid) or DC-5 (also refereed as compound 1 and FIV-50), to search for derivatives that would have similar or better activity, improved aqueous solubility, and reduced toxicity (159). Molecular docking was used to predict the potency and solubility of the new derivatives.…”
Section: Pa Lf and Ef As Antitoxin Design Targetsmentioning
confidence: 99%
“…Left : Structure of compound 22, one of the (M)ANT nucleotides inhibiting with IC 50 = 10 nM (157). Right : Structure for an optimized EF inhibitor, compound 22 (159) inhibiting EF-induced secretion of cAMP by cultured cells with IC 50 = 2.71 μM.…”
Section: Article Highlightsmentioning
confidence: 99%
“…While there was no obvious toxicity to the mice, there was some indication of cytotoxic potential in the “Green Screen” assay at levels 10–20× the active concentration. Our initial results indicated that the fluorenone ring contributed to the inhibitory activity [36], and thus, most of the derivatives synthesized targeted the benzoic acid side chain, which had some markers of toxicity [37]. We were able to identify several derivatives with better predicted pharmaceutical properties, and equivalent or better activity in the bioassay for cAMP production induced by treatment of mammalian cells with ET.…”
Section: Redesign Of the Inhibitors For Enhanced Solubility And Rementioning
confidence: 99%
“…We thus considered that this group should bind in a similar position as the phosphate oxygens of 3'-dATP, and that it would be essential for activity. Further docking analysis of the compound containing the carbamimidoylphenyl derivative indicated that this side chain could target another, negatively charged area of the active site that we had not included in the initial pharmacophore, specifically the backbone oxygen atoms from the residues of Lys346, Gly347, Val350 and carboxyl group of Asp491 [37]. The carbamimidoylphenyl derivative, as it has a lower clogP than compound 1, and no markers of toxicity, has now been included for future animal testing.…”
Section: Redesign Of the Inhibitors For Enhanced Solubility And Rementioning
confidence: 99%